Analisis Pengaruh Ketersediaan, Kualitas Produk, Promosi, dan Harga terhadap Kepuasan Konsumen Pengguna MacBook di Jakarta Selatan - Wadu, Ruth Mariana Bunga; Wirawan, Rio (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of product availability, product quality, promotion, and price on consumer satisfaction with Macbook laptop users in South Jakarta. Through a multiple linear regression analysis approach, this research uses primary data processed using SPSS tools. The results of the validity test show that the research variables are recognized as valid, and the reliability test shows a good level of reliability. VIF analysis confirmed the absence of multicollinearity problems. By using a regression equation, the research results show that product availability, product quality, promotion, and price together influence consumer satisfaction. The individual t-test on these variables produces significant values. Therefore, the hypothesis proposed in this study is accepted. These findings support the importance of promotional strategies in increasing consumer satisfaction and strengthening product positions in the market. The practical implications of this research guide for companies to design more effective marketing strategies, improve product quality, optimize promotions, and design more effective pricing policies to achieve higher consumer satisfaction.